1998
DOI: 10.1007/s005950050171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study on Lung Cancer as a Second Primary Cancer

Abstract: This study evaluates the effect of a previous cancer on the clinical characteristics and the outcome of lung cancer patients. The 313 primary lung cancer patients operated on in the Osaka University Hospital during the period 1984-1993 were reviewed. Of those, 37 had a history of previous cancer. In the lung cancer patients with a history of previous cancer, 20 had adenocarcinomas, 14 had squamous cell carcinomas, while 3 had other cancers. The previous malignancies included 13 gastric cancers, 10 head and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Yet surprisingly, several studies have reported that among newly diagnosed lung cancer patients aged 66 and older, those with a previous cancer do not have worse survival than those with no previous diagnosis; indeed, they often do better. For example, Laccetti et al observed that among patients with a newly diagnosed stage IV lung cancer, those with a previous cancer diagnosis had longer all‐cause survival and lung cancer–specific survival than similar patients who had not had a previous cancer. …”
Section: Introductionmentioning
confidence: 99%
“…Yet surprisingly, several studies have reported that among newly diagnosed lung cancer patients aged 66 and older, those with a previous cancer do not have worse survival than those with no previous diagnosis; indeed, they often do better. For example, Laccetti et al observed that among patients with a newly diagnosed stage IV lung cancer, those with a previous cancer diagnosis had longer all‐cause survival and lung cancer–specific survival than similar patients who had not had a previous cancer. …”
Section: Introductionmentioning
confidence: 99%
“…In a single-center series of 1914 lung cancer patients, of whom 228 (12%) had a history of at least one previous malignancy, no survival detriment was observed in the group with prior cancer (HR = 0.84, 95% CI = 0.70 to 1.01) (22). A number of smaller studies reported similar trends (24,26,27,39). Conversely, in a study of 2991 patients with resected stage I NSCLC, the subset of 192 patients with prior cancer (6%) had statistically significantly inferior survival (HR = 1.44, 95% CI = 1.16 to 1.78) (23).…”
Section: Articlementioning
confidence: 89%
“…Earlier studies investigating the impact of a prior cancer diagnosis on lung cancer outcomes yielded conflicting findings and primarily focused on resected, early-stage lung cancer (22)(23)(24)(25)(26)(27)39). In a single-center series of 1914 lung cancer patients, of whom 228 (12%) had a history of at least one previous malignancy, no survival detriment was observed in the group with prior cancer (HR = 0.84, 95% CI = 0.70 to 1.01) (22).…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Despite these concerns, relatively little is known about the prognostic impact of a prior cancer diagnosis and the appropriateness of this commonplace exclusion criterion. In lung cancer, almost all of the published literature is limited to earlystage resected tumors, and results are conflicted (23)(24)(25). Even less is known about prior cancer diagnoses in patients with locally advanced or metastatic lung cancer, a group accounting for twothirds of all lung cancers and representing the target population of 94% of the lung cancer trials reviewed here.…”
Section: Discussionmentioning
confidence: 99%